Acidically oxidized carbon cloth: a novel metal-free oxygen evolution electrode with high catalytic activity. Issue 9 (12th December 2014) - Cheng, Ningyan; Liu, Qian; Tian, Jingqi; Xue, Yurui; Asiri, Abdullah M.; Jiang, Hongfang; He, Yuquan; Sun, Xuping
Abstract : Acidic treatment of carbon cloth (CC) leads to oxidized CC (OCC) which serves as an efficient metal-free oxygen evolution electrode. Abstract : The efficiency of many energy storage technologies is limited by the sluggish kinetics of the oxygen evolution reaction (OER) and it is thus of great importance to develop highly active OER electrocatalysts made from earth-abundant elements. In this communication, we report a novel metal-free oxygen evolution electrode with high catalytic activity and stability through simple acidic oxidation of commercially available carbon cloth (CC). The resulting acidically oxidized CC exhibits an overpotential of 328 mV and a Tafel slope of 82 mV dec −1 with 100% Faradaic efficiency. This electrode needs an overpotential of 477 mV to afford a current density of 10 mA cm −2 and maintains its catalytic activity for at least 24 000 s. It offers us a low-cost flexible electrocatalytic electrode for device integration toward water splitting and rechargeable metal–air battery applications.